SARS-CoV-2 Genome Sequences, Including One with an ORF7a Deletion, Obtained from Patients in Bangladesh - Rahman, Mizanur; Rahim, Rummana; Hasan, Abu; Kawai, Naoko; Moonga, Lavel Chinyama; Sugi, Tatsuki; Hayashida, Kyoko; Yamagishi, Junya (Microbiology resource announcements, 2021)
Genomic sequences from a complete SARS-CoV-2 open reading frame (ORF) were obtained from 24 patients diagnosed in May 2020 in Dhaka, Bangladesh. All sequences belonged to clade 20A or 20B, and none were variants of concern. Interestingly, one sequence showed a 161-nucleotide deletion in ORF7a. Genomic sequences from a complete SARS-CoV-2 open reading frame (ORF) were obtained from 24 patients diagnosed in May 2020 in Dhaka, Bangladesh. All sequences belonged to clade 20A or 20B, and none were variants of concern. Interestingly, one sequence showed a 161-nucleotide deletion in ORF7a.